Nutrition and functional foods in boosting digestion, metabolism and immune health - Bagchi, Debasis, 1954-; Ohia, Sunny E. (Academic Press, an Imprint of Elsevier, 2022)
"Nutrition and Functional Foods in Boosting Digestion, Metabolism and Immune Health explores the role of appropriate nutrition and digestive enzymes in healthy digestion. The book addresses salient gastrointestinal features involved in healthy digestion pathophysiology, including coverage of the enzyme-microbiome connection and linkage, features of indigestion problems, roles of traditional and conventional ethnic foods, structurally diverse digestive enzymes, drugs, nutraceuticals and novel digestive formulations. In addition, the book addresses technological breakthroughs that have led to recent, novel discoveries and outlines nutritional guidelines and recommendations to achieve healthy digestion"--Publisher's description.